Effects of sludge concentration and biogas sparging rate on critical flux in a submerged anaerobic membrane bioreactor. (December 2017) - Mahmoud, Imad; Liao, Baoqiang
Highlights: Under similar sludge properties, critical flux initially decreased with an increase in MLTS and then reached a flat value. Under similar sludge properties, critical flux initially increased as the biogas sparging rate increased and then reached a flat value. The concept of strict critical flux was not valid for SAnMBRs under sub-critical flux operation. Gel layer formation was the dominant mechanism of membrane fouling under subcritical flux operation. Abstract: Effects of mixed liquor total suspended solids (MLTS) concentration and biogas sparging rate on critical flux of a submerged anaerobic membrane bioreactor (SAnMBR) were systematically studied using an accelerated short-term experiment with a target to minimize the changes of sludge properties. The results show that, under a minimum change of sludge properties, critical flux increased with an increase in the biogas sparging rate, but no further increase was noted after a critical value (6 m 3 /m 2  h) of biogas sparging rate at all tested MLTS concentrations. Similarly, the critical flux decreased with an increase in the MLTS but no further decrease in the critical flux was observed at an MLTS higher than 10.6 g/L for all tested biogas sparging rates. The long-term experiment (over 4.5 months) of the SAnMBR operated at a sub-critical flux showed that gel layer membrane fouling occurred after approximately five weeks operation and thus the concept of strict critical flux was not valid for SAnMBRs.